2016
DOI: 10.1155/2016/9458609
|View full text |Cite
|
Sign up to set email alerts
|

Serial Patch Array Antenna for an FMCW Radar Housed in a White Cane

Abstract: The design, realization, and test of the transmitting and receiving antennas for an FMCW radar operating between 24 and 24.25 GHz (ISM band), to be housed in a white cane for improving mobility of visually impaired subjects, have been performed. The coaxial-to-microstrip transition necessary for feeding the antennas has been studied together with the characteristics of serial arrays of increasing number of patches. Based on this study, a serial array with 8 patches has been selected for the transmitting and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Results of small-sample experiment containing two human subjects showed that the RFID-based smart cane has a potential to help VIPs and blind people to walk independently in indoor environments. Frequency-modulated continuous wave (FMCW) radars and antennas were housed in a classic white cane by Pisa et al [89] for obstacle detection. The result showed that this cane could receive reflections from a metallic panel up to 5 m. FMCW radar is a short-range measuring radar set capable of determining the distance of object in its view field.…”
Section: Vision Substitution By Assistive Canesmentioning
confidence: 99%
“…Results of small-sample experiment containing two human subjects showed that the RFID-based smart cane has a potential to help VIPs and blind people to walk independently in indoor environments. Frequency-modulated continuous wave (FMCW) radars and antennas were housed in a classic white cane by Pisa et al [89] for obstacle detection. The result showed that this cane could receive reflections from a metallic panel up to 5 m. FMCW radar is a short-range measuring radar set capable of determining the distance of object in its view field.…”
Section: Vision Substitution By Assistive Canesmentioning
confidence: 99%
“…Solutions employing 24 GHz radars based on FMCW modulation are presented in [21][22][23], but different choices were made concerning the way the users employ the devices. The clinical investigation was implemented during an observation period of two weeks, using the electromagnetic aid during everyday activities.…”
Section: Electromagnetic Aids For Visually Impaired and Blind Peoplementioning
confidence: 99%
“…Solutions employing 24 GHz radars based on FMCW modulation are presented in [21][22][23], but different choices were made concerning the way the users employ the devices. For both graphs in Figure 6, the answers recorded on the X-axes are: (1) not at all, (2) not much, (3) to some extent, (4) significantly, (5) very significantly.…”
Section: Electromagnetic Aids For Visually Impaired and Blind Peoplementioning
confidence: 99%
See 2 more Smart Citations